Heterozygote to homozygote related living donor liver transplantation in maple syrup urine disease: A case report. (10th February 2015) - Patel, N.; Loveland, J.; Zuckerman, M.; Moshesh, P.; Britz, R.; Botha, J.
Abstract: Liver transplantation is an accepted treatment modality in the management of MSUD. To our knowledge, ours is only the second successful case to date of a patient with MSUD receiving an allograft from an RLD who is a heterozygous carrier for the disease. In view of the worldwide shortage of available organs for transplantation, heterozygote to homozygote transplantation in the setting of MSUD may provide a viable alternative for those awaiting transplantation. We report on the case of a two‐yr‐old infant with MSUD, who received a left lateral segment (segments II and III) liver transplant from his mother, a heterozygote carrier of one of the three abnormal genes implicated in MSUD. Post‐operative BCAA levels normalized in our patient and remained so on an unrestricted protein diet and during times of physiological stress. To date, this is only the second case of a successful RLD liver transplant in a child with MSUD. Preliminary results indicate that RLD liver transplants are at least equivalent to deceased donor liver transplants in the treatment of MSUD, although longer term follow‐up is required. Heterozygote to homozygote RLD transplant in patients with MSUD presents a new pool of potential liver donors.